Relative Selectivity of Plant Cardenolides for Na+/K+-ATPases From the Monarch Butterfly and Non-resistant Insects - Petschenka, Georg; Fei, Colleen S.; Araya, Juan J.; Schröder, Susanne; Timmermann, Barbara N.; Agrawal, Anurag A. (Frontiers in Plant Science, 2018)
A major prediction of coevolutionary theory is that plants may target particular herbivores with secondary compounds that are selectively defensive. The highly specialized monarch butterfly (Danaus plexippus) copes well with cardiac glycosides (inhibitors of animal Na+/K+-ATPases) from its milkweed host plants, but selective inhibition of its Na+/K+-ATPase by different compounds has not been previously tested. We applied 17 cardiac glycosides to the D. plexippus-Na+/K+-ATPase and to the more susceptible Na+/K+-ATPases of two non-adapted insects (Euploea core and Schistocerca gregaria). Structural features (e.g., sugar residues) predicted in vitro inhibitory activity and comparison of insect Na+/K+-ATPases revealed that the monarch has evolved a highly resistant enzyme overall. Nonetheless, we found evidence for relative selectivity of individual cardiac glycosides reaching from four to 94-fold differences of inhibition between non-adapted Na+/K+-ATPase and D. plexippus- Na+/K+-ATPase. This toxin-receptor specificity suggests a mechanism how plants could target herbivores selectively and thus provides a strong basis for pairwise coevolutionary interactions between plants and herbivorous insects.